Language MOOCs: Providing Learning, Transcending Boundaries 2014
DOI: 10.2478/9783110420067.4
|View full text |Cite
|
Sign up to set email alerts
|

4 Motivation in a Language MOOC: Issues for Course Designers

Abstract: Abstract:Whilst several existing studies on foreign language learning have explored motivation in more traditional settings (Dörnyei, 2003), this paper presents one of the first studies on the motivation of participants in a MOOC. The MOOC, Travailler en français (https://sites.google.com/site/mooctravaillerenfrancais/home), was a 5-week open online course for learners of French at level B1 of the CEFR, and aimed to develop language and employability skills for working in a francophone country. It took place i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…Previous studies on SDL have focused on the general perceptions of SDL from students' perspectives (Bonk et al, 2015;Loizzo, Ertmer, Watson, & Watson, 2017) as well as the relations between elements of SDL in MOOCs (Beaven et al, 2014;Kop & Fournier, 2011;Terras & Ramsay, 2015). For example, Terras and Ramsay (2015) examined MOOCs from a psychological perspective, wherein they alluded to some central aspects of SDL, such as motivation and selfmonitoring.…”
Section: Sdl and Self-monitoring In Moocsmentioning
confidence: 99%
“…Previous studies on SDL have focused on the general perceptions of SDL from students' perspectives (Bonk et al, 2015;Loizzo, Ertmer, Watson, & Watson, 2017) as well as the relations between elements of SDL in MOOCs (Beaven et al, 2014;Kop & Fournier, 2011;Terras & Ramsay, 2015). For example, Terras and Ramsay (2015) examined MOOCs from a psychological perspective, wherein they alluded to some central aspects of SDL, such as motivation and selfmonitoring.…”
Section: Sdl and Self-monitoring In Moocsmentioning
confidence: 99%
“…It is concurrent with another study by [26] where they agreed that the learners who enrolled in MOOCs are highly educated. In another study, the majority of participants possessed a good level of education and currently working at the time of taking part in the MOOC [27]. In addition, a different study conducted by [28] has complimented [17].…”
Section: Benefits Of Mooc In Esl Learningmentioning
confidence: 99%
“…Findings from Zhou (2016) in a Chinese MOOC context indicated that autonomous motivation (e.g., intrinsic motivation) plays a central role in terms of continuance intention, and therefore learner-centred design approaches should be a priority for designers. Beaven, Codreanu, and Creuzé (2014) assessed levels of intrinsic motivation in a language MOOC using the Intrinsic Motivation Inventory (IMI; Plant & Ryan, 1985). Perhaps of most relevance in terms of the unique design context of MOOCs, Beaven, Codreanu, and Creuzé (2014) identified factors that created pressure and tension for MOOC participants, including imposed time limits and issues of perceived efficacy.…”
Section: Self-determination Theory In Educational Settingsmentioning
confidence: 99%